2013
DOI: 10.1155/2013/729473
|View full text |Cite
|
Sign up to set email alerts
|

Family Doctors Seen through the Eyes of Specialists: A Qualitative Study

Abstract: Germany is facing a shortage of young family doctors. In search of possible reasons the aim of this study was to explore the perception of specialists on family doctors. Within a qualitative study 16 medical specialists from different fields in hospital and outpatient care setting were interviewed. Interviews were analysed using qualitative content analysis according to Mayring. Most of the interviewed specialists have a positive view on family doctors although a certain depreciative assumption is resonated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…First, considerably fewer female than male GPs and, in particular, fewer female than male dentists participated in the study for unknown reasons. However, the statements of participating male and female GPs did not differ; this finding was also reported by Probst et al [ 18 ] with regard to GPs and specialists. Thus, it is uncertain whether a new perspective would have been added by a more gender-balanced sample.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…First, considerably fewer female than male GPs and, in particular, fewer female than male dentists participated in the study for unknown reasons. However, the statements of participating male and female GPs did not differ; this finding was also reported by Probst et al [ 18 ] with regard to GPs and specialists. Thus, it is uncertain whether a new perspective would have been added by a more gender-balanced sample.…”
Section: Discussionsupporting
confidence: 84%
“…GPs are specialized physicians and (other than dentists) the most visited doctors in Germany [ 13 ]. Although numerous international studies address interprofessional collaboration between GPs and specialists [ 14 18 ], pharmacists or nurses [ 19 22 ], research has neglected cooperation between GPs and dentists. The abovementioned framework of daily practice hinders quantitative and effective health services research at the interface of these areas.…”
Section: Introductionmentioning
confidence: 99%
“…This deterioration can be explained by a preclinical curriculum with very little exposure to primary care experiences, and mostly structured by basic science teaching sessions provided by specialists. It has been reported that specialised physicians tend to convey more or less consciously a negative image of general medicine to students during training [11,12]. The perceptions that changed most after three years essentially dealt with extrinsic factors such as prestige, income, financial risk and career opportunities, whereas many intrinsic factors such as perception of patients' profiles and variety of work changed to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Strangely, they are fast disappearing. [3] However, the National Board of Medical Examination has now said that family doctors are crux because they are the backbone of the healthcare industry.…”
Section: Family Doctormentioning
confidence: 99%